ISLAMIC ETHICAL VISION: . - Michel, Thomas (Journal of Dharma, 1991)
The essence of the Islamic approach to ethics is contained in the very name of the religion, Islam. Faith is a submission of the human will to that of God, performing those deeds which God has commanded and avoiding everything which He has forbidden. Thus, the source and basis of ethical vision for Muslims is what God has taught and commanded, in other words, God’s moral will for humankind as it is to be lived in the personal, familial, social, economic and political spheres.